EFISIENSI SIRKULASI DAN ZONASI PASAR CENGKARENG - Olivia Iendah Permatasari (Jurusan Arsitektur dan Perencanaan, 2022)
The market for most people is a place to live, earn a living, also a place for people to meet and interact to meet individual needs. Traditional market offerings have many advantages, including much cheaper prices, variety of food ingredients that can be seen directly, many of the necessities that are served can be negotiated. The traditional market is a representation of the people's economy, with sufficient class economic capacity, and a reliable place for small and medium scale businesses. The existence of traditional markets in the face of digital acceleration is a formidable challenge in the midst of global competition and the urgency of the pandemic drive. The modern market is getting stronger by the day and actively attracts buyers by means of all the advantages it has to offer. while the traditional market still bears the stigma of “dirty; uncomfortable; unhygienic” compared to modern markets. Therefore, traditional markets are starting to lose their interest, especially for Generation Z, which is already very dependent on digital products. To avoid being abandoned by consumers and being able to compete in the modern market, therefore the quality of service and management of traditional markets must be improved, by increasing circulation and zoning efficiency in order to support market needs with current market activities with digital intervention. The author tries to provide new space for visitors, sellers and managers with the super-imposition method between the circulation of building users. Keywords: Circulation, Zoning AbstrakPasar bagi sebagian besar masyarakat adalah tempat untuk hidup, mendapatkan kehidupan, juga tempat untuk orang bertemu dan berinteraksi untuk memenuhi kebutuhan individu. Penawaran pasar tradisional memiliki banyak keuntungan, diantaranya harga jauh lebih murah, variasi bahan pangan yang dapat dilihat langsung, banyak barang kebutuhan yang disajikan dapat ditawar. Pasar tradisional merupakan representasi perekonomian rakyat, dengan kemampuan ekonomi kelas terbilang cukup, dan tempat yang dapat diandalkan untuk skala kecil dan menengah . Eksistensi pasar tradisional menghadapi percepatan digital merupakan tantangan yang berat di tengah persaingan global dan urgensi dari dorongan pandemi. Pasar modern semakin kuat dari hari ke hari dan aktif menarik pembeli dengan sarana dari segala kelebihan yang ditawarkan. sementara pasar tradsional masih menyandang stigma “kotor;tidak nyaman; tidak higenis” dibandingkan dengan pasar modern. oleh karena itu, pasar tradisional mulai kehilangan minatnya terlebih pada generasi Z yang sudah sangat bergantung pada produk digital. Untuk menghindari ditinggalkan konsumen serta mampu bersaing di pasar modern, oleh karena itu kualitas pelayanan dan pengelolaan pasar tradisional harus ditingkatkan, dengan cara meningkatkan efisiensi sirkulasi dan zonasi demi menunjang kebutuhan pasar dengan aktivitas pasar saat ini dengan intervensi digital. Penulis berusaha memberi ruang gerak baru kepada pengunjung , penjual dan pengelola dengan metode super-imposisi antara sirkulasi pengguna bangunan.